DETERMINANTS OF FINANCIAL TECHNOLOGY USE: QRIS (Quick Response Code Indonesian Standard) PRODUCTS IN GEN Z (Study on Private University Students in Bandar Lampung) - Fitri Ahyani; Luke Suciyati Amna; Khairudin (International Journal of Economics, Business and Innovation Research, 2024)
This research focuses on the role of QRIS as a digital payment tool in replacing cash. QRIS, released by Bank Indonesia, aims to provide facilities in the form of non-cash transactions, especially among Generation Z students. Investigate the influence of perceived benefits, ease of use, and risk on the interest of private students in Bandar Lampung when using QRIS as a means of payment. Quantitative research methods were conducted on 85 students from 5 universities and 7 study programs. The results show that perceived benefits do not have a significant impact on interest in using QRIS, while perceived convenience has a positive and significant effect. Perceived risk also has a positive and significant impact on interest in using QRIS, indicating that students who have a high awareness of risk are more likely to choose QRIS as a payment method. The conclusions of this study can be the basis for increasing understanding and acceptance of QRIS among Generation Z students as a means of payment. Keywords: QRIS, GenZ, Perceived Benefits, Perceived Ease, Perceived Risk, Usage Decision.